The Influence of Digital Leadership and Digital Competence on the Performance of Printing Employees in Karawang - Lia Putri, Imel; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
Due to digital transformation, companies face great challenges in adapting to technological advancements. As part of the creative industry, the digital printing sector has been heavily impacted by these changes. Therefore, this study aims to look at how digital leadership and digital competencies affect employee performance in the digital printing industry. This research was conducted quantitatively and has a cross-sectional design. This study involved all employees of digital printing companies in Karawang, with 103 respondents. Data is collected through questionnaires that are shared with employees working in the field. The hypothesis that digital leadership has a positive effect is rejected because the results of the analysis show that it has no significant effect on employee performance. In contrast, digital competencies have been shown to have a significant influence on employee performance; Good digital competencies allow for faster and more accurate completion of tasks, which in turn results in improved performance. In addition, employee performance is significantly influenced by both digital leadership and competence. According to the R-Square (R2) value of 0.473, these two variables contribute significantly to changes in overall employee performance.